Taxanomic status of Phenacoccus transcaucasicus Hadz. (=Ph. mespili sensu Borchsenius, 1949) and its intraspecific variability (Homoptera, Coccinea, Pseudococcidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The wide distribution and polyphagy of Phenacoccus aceris Signoret, 1875, resulted in numerous synonyms, some of them still used as valid names by some authors. One of such names is P. mespili Signoret, 1875. Synonymy of this name with P. aceris was mentioned by some authors (Newstead, 1903; Lindinger, 1912, etc.). Borchsenius (1949) considered it a separate species and published a redescription, with records from the former USSR. Ter-Grigorian (1973) and Tereznikova (1975) followed his concept and published the drawings of the respective species. Ben-Dov and Matile-Ferrero (1995) examined the types of P. aceris and P. mespili from the collection of Signoret in Vienna and confirmed the synonymy of P. mespili with P. aceris. Examination of material identified by Borchsenius as P. mespili from the collection of Zoological Institute in St.Petersburg, has shown that it belongs to P. transcaucasicus Hadzibejli, 1960. The descriptions and drawings by Ter-Grigorian (1973) and Tereznikova (1975) also refer to this species.The species recorded from Italy by Marotta (1990) as P. mespili, judging by the description and drawing, belongs neither to P. aceris, not to P. transcaucasicus. It differs from P. transcaucasicus in the fewer multilocular disc pores and ventral tubular ducts. Records of "P. mespili" from Hungary (Kosztarab & Kozar, 1988) are not confirmed by material (F. Kozar, personal communication).P. transcaucasicus is known from the South of the European Russia, Ukraine, Transcaucasia and Central Asia. It lives on the twigs and trunks of fruit-trees of the family Rosaceae and also on Fraxinus, Juglans and Lonicera. The intraspecific variability of P. transcaucasicus in the number of dorsal tubular ducts is very wide (from entire absence to presence of transverse rows on the thorax and abdomen). It is not associated with distribution or host plants: the extremes and intermediates may occur in the same series.
Keywords: Phenacoccus aceris; synonymy; valid names; collection of Signoret; dorsal tubular ducts